2017
DOI: 10.1159/000478017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Influenza Vaccination on Risk of Stroke: A Systematic Review and Meta-Analysis

Abstract: Background: Despite the presence of a strong association between influenza infection and stroke, whether influenza vaccination reduces the risk of stroke is yet a matter of controversy. We conducted a meta-analysis to determine whether influenza vaccination protects against stroke. Methods: We searched PubMed, EMBASE, and the Cochrane Library from database inception date to November 18, 2016, without language restrictions, to identify studies investigating the effect of influenza vaccination on subsequent risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 40 publications
(60 reference statements)
3
28
0
3
Order By: Relevance
“…They reported that respiratory viruses except parain uenza were signi cantly associated with ischemic stroke admission in the elderly (≥ 75 years). In particular, in uenza was widely discussed in the scienti c discourse because an in uenza vaccination is available and may possibly lead to a risk reduction [44]. However, the evidence is limited due to the lack of randomized controlled studies.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that respiratory viruses except parain uenza were signi cantly associated with ischemic stroke admission in the elderly (≥ 75 years). In particular, in uenza was widely discussed in the scienti c discourse because an in uenza vaccination is available and may possibly lead to a risk reduction [44]. However, the evidence is limited due to the lack of randomized controlled studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the impact of influenza vaccination in older adults demonstrate reductions in the incidence of stroke and acute myocardial infarction of approximately 20% and studies in at-risk older patients with at least one co-morbidity show a clear dose-effect over multiple influenza seasons [43,44]. There are some indications that pneumococcal vaccination of older adults can also reduce the risk of cardiovascular disease, though the association is weaker than that reported for zoster or influenza [45,46]. Vaccination can markedly reduce demand for health services by older adults.…”
Section: The Full Burden Of Vaccine-preventable Diseasementioning
confidence: 99%
“…Lin et al 45 identificaram, em estudo de caso-controle, que idosos vacinados apresentavam menor risco de internação por AVC (OR = 0,76, IC95%: 0,60; 0,97) e que o risco diminuiu com o número crescente de vacinas (revacinação anual). Recentemente, uma revisão sistemática de estudos observacionais com metanálise também mostrou que a vacinação está associada a um risco menor de AVC, visto que indivíduos vacinados apresentaram menor risco em comparação aos indivíduos não vacinados (OR = 0,82, IC95%: 0,75; 0,91, p < 0,001) 48 .…”
Section: Sexo/faixa Etária (Anos)/períodosunclassified